Reversed L-type matching impedance of RF-to-DC rectifier for energy harvesting system / Nuraiza Ismail and Ermeey Abd Kadir - Ismail, Nuraiza; Abd Kadir, Ermeey (Universiti Teknologi MARA, 2021)
This paper presents the analysis of an RF energy harvesting system using a novel design of harvester antenna and wirelessly connected to reversed L-type matching impedance integrated with a 2-stage rectifier circuit. The rectifier circuit is based on a voltage doubler-type topology comprising only two circuit components which are a capacitor and Schottky diode that are capable of receiving a Wi-Fi input signal of 2.45 GHz from a harvester antenna. The antenna design is a rectangular patch antenna that is based on a coplanar waveguide feed. The zero biased Schottky diode of the SMS7630 model is chosen for the rectification process where the low input signal of -10dBm has successfully rectified the RF input power to the DC output voltage. The simulation results show that the 2-stage rectifier circuit needs impedance matching for a better DC output voltage with a good power conversion efficiency than a rectifier circuit without impedance matching for enabling low-power electronic devices.